Mathematical model for the bulk polymerization of styrene using the symmetrical cyclic trifunctional initiator diethyl ketone triperoxide. I. Chemical initiation by sequential decomposition. Issue 1 (17th July 2012) - Berkenwald, E.; Spies, C.; Cortez, J. R. Cerna; Morales, G.; Estenoz, D.
Abstract In this study, we experimentally and theoretically investigated the use of the symmetrical cyclic trifunctional initiator diethyl ketone triperoxide (DEKTP) in the bulk polymerization of styrene. The experimental study consisted of a series of isothermal batch polymerizations at different temperatures (120 and 130°C) with different initiator concentrations (0.005, 0.01, and 0.02 mol/L). A mathematical model was developed to predict the evolution of the reacting chemical species and the produced molecular weight distributions. The kinetic model included chemical and thermal initiation, propagation, transfer to the monomer, termination by combination, and reinitiation reactions. The simulation results predict the concentration of diradicals, monoradicals, and polymeric chains, characterized by the number of undecomposed peroxide groups. The experimental results showed that at reaction temperatures of 120–130°C, initiation by DEKTP produced an increase in the polymerization rates (Rp's) and average molecular weights, depending on the initiator concentration, due to sequential decomposition. The mathematical model was adjusted and validated with the experimental data. The theoretical predictions were in very good agreement with the experimental results. Also, an optimum initiator concentration was observed that achieved high Rp's and high molecular weights simultaneously. For polymerization temperatures of 120–130°C, the optimum concentration was 0.01 mol/L. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013